VCP5-DVC official cert training VMware certified professional : data center virtualization (Exam VCP 550) - Ferguson, Bill.; Safari eBooks ([S.l.] : VMware Press, 2014)
"Bill Ferguson, VCI (3,4,5), VCP (3,4,5), MCT, MCSE, MCP+I, CCNA, A+, Network+, Server+, has been in the computer industry for more than 15 years. Originally in technical sales and sales management with Sprint, Bill made his transition to Certified Technical Trainer in 1997 with ExecuTrain. Bill now runs his own company as an independent contractor in Birmingham, Alabama, teaching classes for most of the national training companies and some regional training companies and corporations. In addition, Bill writes and produces technical training videos for Virtual Training Company, Inc. and Specialized Solutions, Inc. His current titles include A+, Network+, Windows 2000 Management, Windows XP Management, Windows 2000 Security, Server+, and Interconnecting Cisco Network Devices. Bill keeps his skills sharp by being a technical reviewer for books and sample tests. Bill says, 'My job is to understand the material so well that I can make it easier for my students to learn than it was for me to learn.'"--Resource description page.
Title from resource description page (viewed Mar. 10, 2014).
Presenter, Bill Ferguson.
Keywords: VMware; VMware vSphere; Virtual computer systems; Computer networks -- Access control; Computer security; Client/server computing; Electronic data processing personnel -- Certification; Electronic books